(untitled) (Journal of Production Engineering, 2023)
Form tool means a cutting tool which is appropriate manufacturing of workpieces having more complicated geometry. The contour of manufactured workpiece is manufactured by the tool profile. This cutting tool can be used in case of serial and quantity production. The advantageous of their usage are the lower turning time and the lower standard deviation of the workpiece sizes. The reached accuracy on the workpiece is independent from the qualification of the worker. The aim of this publication is the explanation of the geometric analysis and the design by analytical and constructional way. This type of tool is advantageously usable for manufacturing on CNC machine or conventional machine.